Probabilistic Modeling of Failure Domino Effects in Chemical Plants - Sierra, Diego; Briceño, Juan; Buitrago, Hector; Rozo, Brian; Montecchi, Leonardo; Mura, Ivan (Anais do Latin-American Symposium on Dependable Computing (LADC); 2018: Anais do VIII Latin-American Symposium on Dependable Computing, 2018)
Chemical process plants are subject to risk caused by the handling and storage of hazardous substances. Major accidents may occur, particularly in those unfortunate circumstances when a triggering event produces a cascading accident that propagates to other units, a failure propagation scenario known as domino effect. An important aspect of designing such industrial plants is to properly arrange hazardous equipment such that, in the event of failures, cascading effects are minimized. In this work, we present a modeling approach to perform a probabilistic analysis of the likelihood of domino effects caused by propagating vapor cloud explosions. The approach combines the modeling of accident propagation based on physical properties of gas clouds, such as released mass and explosion distance, with the probabilistic modeling of cascading effects based on Stochastic Petri Nets. The proposed methodology is subsequently applied to a case study where different layouts of atmospheric gasoline tanks are analyzed, in order to evaluate the likelihood of domino effect occurrence.